2001
DOI: 10.1590/s0104-79302001000200003
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial activity of propolis produced by Apis mellifera L. and Brazilian stingless bees

Abstract: This study investigated the antibacterial activity of propolis produced by A. mellifera and Brazilian stingless bees, called "meliponíneos". Susceptibility tests to ethanolic extracts of propolis (EEP) were performed using bacterial strains (Staphylococcus aureus, Enterococcus sp, and Escherichia coli) isolated from human infections. Dilution of EEP in agar (%v/v) was used for determination of minimal inhibitory concentration (MIC). The stingless bee species (and common names) were: Nannotrigona testaceicornis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 15 publications
0
18
0
5
Order By: Relevance
“…In Brazil for instance, Africanized bees (Apis mellifera scutellata) are found in addition to native South American bees (e.g. Melipona and Tetragonisca species) (Sheppard et al, 1991;Fernandes Jr et al, 2001). The former bee type tends to gather bud exudates of the plant Baccharis dracunculifolia (Asteraceae), whereas European bees (other Apis mellifera L. subspecies), common in temperate zones, collect bud exudates of poplar trees (Kumazawa et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Brazil for instance, Africanized bees (Apis mellifera scutellata) are found in addition to native South American bees (e.g. Melipona and Tetragonisca species) (Sheppard et al, 1991;Fernandes Jr et al, 2001). The former bee type tends to gather bud exudates of the plant Baccharis dracunculifolia (Asteraceae), whereas European bees (other Apis mellifera L. subspecies), common in temperate zones, collect bud exudates of poplar trees (Kumazawa et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The former bee type tends to gather bud exudates of the plant Baccharis dracunculifolia (Asteraceae), whereas European bees (other Apis mellifera L. subspecies), common in temperate zones, collect bud exudates of poplar trees (Kumazawa et al, 2002). Previous studies have revealed differences in antibacterial and antifungal activity of propolis extracts attributable to a difference in chemical composition and concentration of propolis compounds depending on the bee type involved in collection (Fernandes Jr et al, 2001;Silici and Kutluca, 2005;.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Martinez Garcia et al (14) ;Duailibe et al (15) Clinical -Antimicrobial action Azevedo et al (4) ;Santos et al (11) ; Lofuto et al (35) Clinical -Therapeutic action in wound healing Peruchi et al (2) ;Park et al (3) ;Vargas et al (5) ; Fernandes Júnior et al (6) ; Silva et al (7) ;Sforcin et al (8) ; Sforcin et al (9) ;Oliveira et al (10) ; Auricchio et al (35) ; Fernandes Júnior et al (17) ;Machado et al (18) ;Longhini et al (19) ;Sawaya et al (20) ;Fernandes et al (21) ;Fernandes Júnior et al ( 22) ; Muli et al (23) ;Gebara et al (24) ;Fernandes Júnior et al (25) ;Bianchini et al (26) ;Gonçales et al (27) ;Dantas et al (28) ; Ayres et al (29) ;Orsi et al (30) ;Orsi et al (31) ;Sforcin et al (32) ;Sforcin et al (33) ;Orsi et al (34) ; Fernandes Júnior et al (36) ;Fernandes et al (37) ; Araújo et al (38) Experimental -Antimicrobial action Rahal et al (16) Experimental -Therapeutic action in wound healing (1) . Another study, which used propolis ointment on 22 chronic wounds, of which 11 were venous ulcers, seven pressure ulcers, two diabetic ulcers, and two post-trauma injuries, found that necrotic tissue was present in 14 (8.2%) during tissue assessment process.…”
Section: Thematic Focus Approachmentioning
confidence: 99%